2011
DOI: 10.1167/iovs.10-6144
|View full text |Cite
|
Sign up to set email alerts
|

Visual Suppression in Intermittent Exotropia during Binocular Alignment

Abstract: Antidiplopic mechanisms in X(T) can be reliably triggered by purely retinal information during orthotropia, but the nature of these mechanisms varies between patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 32 publications
2
45
1
1
Order By: Relevance
“…Suppression did not occur if only motor signals revealed the deviation of eyes when we projected rivalry-free images onto corresponding retinas. Together with study by SerranoPedraza et al, 14 the results represent the sensory mechanism of suppression. The findings correlated well with the clinical observation that X(T) patients who undergo successful strabismus surgery usually show good and persistent binocularity after surgery, even though the proprioceptive feedback and motor state in the brainstem is not changed.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Suppression did not occur if only motor signals revealed the deviation of eyes when we projected rivalry-free images onto corresponding retinas. Together with study by SerranoPedraza et al, 14 the results represent the sensory mechanism of suppression. The findings correlated well with the clinical observation that X(T) patients who undergo successful strabismus surgery usually show good and persistent binocularity after surgery, even though the proprioceptive feedback and motor state in the brainstem is not changed.…”
Section: Discussionsupporting
confidence: 78%
“…Several studies have proven the existence of suppression via psychophysical or electrophysiological methods. 11,14,16 Maurits et al 16 demonstrated the existence of suppression by recording the visual evoked potential in strabismic patients, both in esotropia and exotropia. The visual evoked potential response was decreased in the binocular state in all participants, and suppression was irrelevant to the extent of the amblyopia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has a prognostic significance and we suggest this as a cutoff beyond which only cosmetic correction, but no functional gain, is expected. The non-improvement of distance stereoacuity can be attributed to central suppression 8 15…”
Section: Discussionmentioning
confidence: 99%
“…62 In healthy controls, although cyclopean stereo vision can be demonstrated in infants at B3 months, 63,64 stereoacuity continues to improve up to the age of B10 years. [65][66][67][68][69][70] This long period of plasticity implies that binocular vision remains vulnerable to disruption until later in development, for example, by the onset of accommodative esotropia in toddlerhood. 71 Conversely, the window for recovery remains open for longer.…”
Section: The Clinical Importance Of Stereoacuity Measurementsmentioning
confidence: 99%